ОПТИМІЗАЦІЯ ВИКОРИСТАННЯ ДОСТУПНИХ ЕНЕРГОРЕСУРСІВ МІКРОМЕРЕЖІ ЗА УМОВ ПІДТРИМКИ ГОТОВНОСТІ ДО ІЗОЛЬОВАНОГО РЕЖИМУ - Парус, Є.В.; Блінов, І.В. (Інститут електродинаміки НАН України, Київ, 2025)
The paper presents methods and models for solving problems of planning the operating modes of a microgrid. The main goal of optimization is to minimize the cost of electricity purchased from the electricity supplier. The task of maintaining the readiness state of energy storage systems is solved by solving additional optimization problems and is given by a system of constraints. The objective function of optimization problems and a system of equations of electricity balances are presented. A mathematical model for simulating the operating modes of an energy storage unit as the main means of balancing energy flows in a microgrid has been developed. A mathematical model for simulating the functions of controlling energy flows from a solar station as the main means of unregulated electricity generation in a microgrid has been developed. A mathematical model for solving the problem of minimizing the costs of purchasing electricity to ensure the readiness of the microgrid for the isolated mode has been developed. A mathematical model for solving the problem of minimizing the costs of purchasing electricity for the microgrid’s own electricity consumption has been developed. A methodology for estimating the amount of energy reserve required to support critical electricity consumption in the isolated mode has been developed. A methodology for comprehensively solving the tasks of planning the operating modes of power equipment in a microgrid has been developed. An example of calculations for performing the tasks of planning the operating modes of a microgrid has been given. Based on the results of the calculations, the peculiarities of the formation of electricity balances in a microgrid have been analyzed. References 25, figures 5.